PENGARUH METODE MONTESSORI TERHADAP HASIL BELAJAR SISWA PADA TEMA VIII DAERAH TEMPAT TINGGALKU KELAS IV SD NEGERI 035938 DESA RENUN - Br Simanjuntak, Jelita; Aton Sitepu; Patri Janson Silaban; Rumiris Lumbangaol; Antonius Remigius Abi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the Montessori method on student learning outcomes in theme VIII in the area where I live, class IV at state elementary school 035938 Desa Renun for the 2024/2025 academic year. In this study using quantitative methods, the population of this study was all class IV of SD Negeri 035938 Desa Renun, totaling 25 students consisting of 10 boys and 15 girls. Sampling was taken using purposive sampling and the sample used was class IV, totaling 25 students. The results of this research show that student learning outcomes using the Montessori method are included in the good category with an average of 80,2 with a correlation test result of 0.808, which means rcount (0.808) ≥ rtable (0.396), so Ha is accepted. So there is a very strong influence between the use of the Montessori method on student learning outcomes in theme VIII in the area where I live, class IV at SD Negeri 035938 Desa Renun. It can be seen from the results of the T-test research where tcount ≥ ttable is 5,163 ≥ 1.708 so it can be stated that Ha is accepted. This shows that there is a significant positive influence from the use of the Montessori method on student learning outcomes in theme VIII in the area where I live, class IV of SD Negeri 035938 Desa Renun for the 2024/2025 academic year.